The Influence of Communication, Information, and Education (KIE) Through Leaflet and Video Media on Adolescents' Knowledge and Attitudes About Exposure to Pornography - Ahmad Maulana; Ahmad Rasyid As-Syai; Muhammad Irsahwandi; Mardianto Mardianto; Haidir Haidir (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The research objective was to determine the influence of KIE (communication, information, and education) through leaflets and video media on adolescents’ knowledge and attitude toward pornographic exposure. The research used quasi experimental method. The population was all Grades VII and VIII students of SMP Negeri 45 Medan, and 60 of them were used as the samples, which consisted of 30 respondents in the leaflet group and the other 30 respondents in the video group. The analysis showed an influence of counseling with leaflet media about pornographic exposure on students’ knowledge (p=0.000) and attitude (p=0.000). There was an influence of counseling with video media about pornographic exposure on students’ knowledge (p=0.0000 and attitude (p=0.000). Video media was more effective in increasing knowledge (p=0.000) and attitude than leaflet media in counseling about pornographic exposure. It is recommended that the students be more proactive in counseling about pornography which influences reproductive health and uses leaflets and videos as the media to increase their behavior in forestalling pornographic exposure.